TECHNOLOGY OF SATELLITE AND PHOTO IMAGES FREQUENCY-RESONANCE PROCESSING: ON PROSPECTS OF LARGE OIL AND GAS FIELD DISCOVERING WITHIN IRONBARK STRUCTURAL UPLIFT ON AUSTRALIAN OFFSHORE - Mykola Yakymchuk; Ignat Korchagin (Research Retrieval and Academic Letters, 2023)
The results of application of mobile direct-prospecting technology of frequency-resonance processing and interpretation of satellite images and photographs at the areas and sites of exploratory wells drilling on the Australia offshore and onshore are presented. Experimental research of a reconnaissance nature was carried out with the aim of demonstrating the efficiency, effectiveness and informativeness of direct-prospecting methods. During frequency-resonance processing a satellite image of the Ironbark-1 well location site at December, 2020, signals of oil, condensate, gas, and phosphorus (white) were recorded from the surface and on the hydrocarbon’s synthesis surface of 57 km. Signals of the 7th group of sedimentary rocks (limestones) have been registered also. The root of the limestone-filled volcano was identified at a depth of 723 km. The migration of gas and phosphorus into the atmosphere was confirmed by instrumental measurements. Such results allow to conclude about high probability of hydrocarbon deposits detecting within the Ironbark-1 well drilling area. Unfortunately, the Ironbark-1 exploratory well drilled within the structure at the end of 2020 was declared empty. But the results of investigation at December, 2020 allowed the authors to conclude that the Ironbark-1 well has not been drilled to productive horizons (intervals)! On August 20, 2023, additional instrumental measurements were carried out at the drilling site with procedures of cross-section vertical sounding using. During cross-section scanning from 5630 m to 7000 m, step 5 cm, responses at oil frequencies were recorded from the following intervals: 1) 5634.5-5824 m, 2) 5843.5-6252 m, 3) 6368-6718 m. From the interval of 7-10 km, responses at the frequencies of oil were also recorded. Oil signals were recorded again at a depth of HC synthesis of 57 km! The results of scanning at the drilling site confirmed the authors assumption that the Ironbark-1 well was not drilled to productive intervals and suggest also that there is a major oil and gas deposit within the Ironbark structure! In this regard, it is advisable to continue further prospecting and the wells drilling within its limits. In order to demonstrate the additional possibilities of direct-prospecting methods, the results of a reconnaissance survey at the drilling sites of three more wells on the Australia offshore and onshore are presented in paper also. Reconnaissance studies carried out on the offshore and onshore of Australia indicate that mobile direct-prospecting methods can be used to assess the prospects of oil and gas potential (ore potential) of large prospecting blocks and local areas (including those put up for auction), the selection of optimal locations (sites) of exploratory and production wells, assessment of the prospects of oil and gas deposits discovering in the deep horizons of cross-section, searches and localization of deep channels for the migration of chemical elements, fluids and mineral matter into the upper horizons of cross-section. The use of mobile and low-cost technology will significantly speed up the geological exploration process for hydrocarbons, natural hydrogen, ore minerals, as well as reduce financial costs for its implementation.